THE EFFECT OF GOOD GOVERNANCE ON FOOD SECURITY IN INDONESIA: AN EMPIRICAL ANALYSIS - Jhon Hendra; Sri Pratiwi Saraswati Dewi; Septia Wahyu Elda; Suryandaru Suryandaru (Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study aims to analyze the influence of good governance on food security in Indonesia using time-series data from 2002 to 2023. The good governance indicators employed include government effectiveness, control of corruption, and political stability, while food security is measured by the Food Consumption Pattern Score (Pola Pangan Harapan, PPH). The regression analysis results show that the model is statistically significant, with a coefficient of determination (R²) of 92%, indicating that a substantial proportion of the variation in food security can be explained by the good governance variables. Individually, all three independent variables have a significant effect on food security (t-test, p < 0.05), with government effectiveness exhibiting the strongest contribution. These findings reinforce the qualitative analysis that improving bureaucratic capacity, strengthening anti-corruption oversight, and maintaining political stability are important prerequisites for building an equitable and resilient food system. Corrupt practices in food procurement, bureaucratic inefficiencies, and policy fluctuations driven by political instability have so far weakened food security, especially among vulnerable groups. Therefore, institutional improvements in good governance, through strengthened regulations, public accountability, and community participation, represent key strategies for sustainably enhancing Indonesia’s food security.